Who Is Afraid of Love? Adam Smith and the Rational Analysis of Bonding - Elias L. Khalil (20518877) (2025)
For Smith, love inextricably involves negative feelings, what this paper calls “bonding cost”. The bonding cost can be moderate. However, it can easily become excessive, taking the form of turbulent emotions, obsessions, vulnerabilities, and ego-centrism. Hence, it is no wonder that Smith is highly critical of love. However, paradoxically, Smith also embraces love, as it nurtures individual development and family warmth. Should we therefore conclude that Smith is inconsistent? Not necessarily if we introduce rational choice theory to the analysis of love and bonding—which Smith calls “mutual sympathy.” Rational choice theory allows us to identify the suboptimal level of love, namely, when bonding costs (i.e., obsessions and emotional upheavals) exceed the benefits of love (the nurture of individual development and family warmth). Otherwise, when the benefits of love equal bonding costs, the level of love is optimal. Furthermore, another thesis of the paper, the proposed rational analysis of bonding should not mean that bonding and material/substantive motives/preferences are commensurable. The distinction of love-based preferences (bonding) from substantive-based preferences (material satisfaction) challenges us to identify exactly how love differs from substantive satisfaction—a challenge that this paper undertakes. Other Information Published in: Theoria License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://doi.org/10.1111/theo.70022